2015
DOI: 10.1038/srep12318
|View full text |Cite
|
Sign up to set email alerts
|

The variability and seasonality of the environmental reservoir of Mycobacterium bovis shed by wild European badgers

Abstract: The incidence of Mycobacterium bovis, the causative agent of bovine tuberculosis, has been increasing in UK cattle herds resulting in substantial economic losses. The European badger (Meles meles) is implicated as a wildlife reservoir of infection. One likely route of transmission to cattle is through exposure to infected badger urine and faeces. The relative importance of the environment in transmission remains unknown, in part due to the lack of information on the distribution and magnitude of environmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 29 publications
1
50
0
Order By: Relevance
“…Negative samples were prepared in a double-blind manner and randomly introduced into the experiment at both laboratories. As this qPCR assay is highly specific for M. bovis (25), all false-positive findings are expected to result from contamination introduced in the laboratory; therefore, negative controls were included at every stage of DNA extraction and quantification.…”
Section: Methodsmentioning
confidence: 99%
“…Negative samples were prepared in a double-blind manner and randomly introduced into the experiment at both laboratories. As this qPCR assay is highly specific for M. bovis (25), all false-positive findings are expected to result from contamination introduced in the laboratory; therefore, negative controls were included at every stage of DNA extraction and quantification.…”
Section: Methodsmentioning
confidence: 99%
“…The necropsy examination included detailed macroscopic inspection of lymph nodes and abdominal and thoracic viscera ( 6 ). We found no TB-like visible lesions; pooled tissue samples (retropharyngeal, tracheobronchial, mediastinal, and mesenteric lymph nodes) were submitted bacterial culture and molecular diagnosis ( 6 ); urine, feces, and oropharyngeal swabs were taken, and DNA was extracted as previously described ( 7 ). We performed molecular diagnostic testing using MTBC PCR (IS 6110 and IS 1081 ) and the regions of difference and through spoligotyping ( 6 ), the latter 2 enabling differentiation of the MTBC members when used on highly concentrated DNAs.…”
mentioning
confidence: 99%
“…In Great Britain, it is reported that the incidence in cattle declined to 0.01% in the end of the 1970s, but the incidence in the year 2010 reached 5%, and in the UK the disease will lead to over 1 million pounds over the next 10 years [1].…”
Section: Introductionmentioning
confidence: 99%
“…These variables are the recurrence of bovine tuberculosis disease in the same settlement areas [6] animal movements [4] and seasonality [1,7,8]. From these variables, seasonality is defined as the periodic occurrence of events at a certain time [8].…”
Section: Introductionmentioning
confidence: 99%